Pengaruh Penerapan Model Cooperative Learning dengan Mind Mapping terhadap Hasil Belajar Tematik Siswa Kelas III SD - Meliyani, Mila; Salimi, Asmayani; Pranata, Rio (FONDATIA, 2023)
Implementation of thematic learning is carried out using conventional learning models which cause students to still have difficulty understanding lessons. To improve understanding and student learning outcomes, appropriate models and strategies are needed. The purpose of this research is to find out how the thematic learning outcomes of students apply the cooperative learning model with mind mapping. This study used an experimental method in the form of a quasi-experimental design. Sampling using purposive sampling technique was used to select 31 students from class III A as the experimental class, and 30 students from class III B as the control class. Using measurement techniques for data collection. The instrument used is in the form of multiplechoice questions of 50 questions. By using Microsoft Excel in testing the hypothesis, the tcount is 3.6422 and the ttable for the significance level (5% and dk 31+30-2+59) is 2.000. If tcount > ttable, then Ha is accepted which indicates that the cooperative learning model with mind mapping has an effect on the thematic learning outcomes of class III students at SD Negeri 39 Pontianak Kota.